Mitochondrial Bioenergetics Is Altered in Fibroblasts from Patients with Sporadic Alzheimer's Disease - Pérez, María J.; Ponce, Daniela P.; Osorio-Fuentealba, Cesar; Behrens, Maria I.; Quintanilla, Rodrigo A. (Frontiers in Neuroscience, 2017)
The identification of an early biomarker to diagnose Alzheimer's disease (AD) remains a challenge. Neuropathological studies in animal and AD patients have shown that mitochondrial dysfunction is a hallmark of the development of the disease. Current studies suggest the use of peripheral tissues, like skin fibroblasts as a possibility to detect the early pathological alterations present in the AD brain. In this context, we studied mitochondrial function properties (bioenergetics and morphology) in cultured fibroblasts obtained from AD, aged-match and young healthy patients. We observed that AD fibroblasts presented a significant reduction in mitochondrial length with important changes in the expression of proteins that control mitochondrial fusion. Moreover, AD fibroblasts showed a specific alteration in proteolytic processing of OPA1, a master regulator of mitochondrial fusion, compared to control fibroblasts. Complementary to these changes AD fibroblasts showed a dysfunctional mitochondrial bioenergetics profile that differentiates these cells from aged-matched and young patient fibroblasts. Our findings suggest that the human skin fibroblasts obtained from AD patients replicate mitochondrial impairment observed in the AD brain and suggest that the analysis of mitochondrial bioenergetics in these cells could represent a promising strategy to develop new diagnostic methods in peripheral tissues of AD patients.